2020
DOI: 10.3389/fpls.2020.00878
|View full text |Cite
|
Sign up to set email alerts
|

Weedy Rice as a Novel Gene Resource: A Genome-Wide Association Study of Anthocyanin Biosynthesis and an Evaluation of Nutritional Quality

Abstract: The pericarp color of rice grains is an important agronomic trait affected by domestication, and the color pigment, anthocyanin, is one of the key determinants of rice nutritional quality. Weedy rice, also called red rice because its pericarp is often red, may be a novel gene resource for the development of new rice. However, the genetic basis and nutritional quality of anthocyanin are poorly known. In this study, we used a genome-wide association study (GWAS) to find novel and specific QTLs of red pericarp in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The elucidation of the genetic determinants of the diversity of important traits through GWAS can help us to identify strong alleles and provides a theoretical basis for us to obtain biofortified crops and on agriculturally important traits such as shoot apical meristem (Leiboff et al, 2015), heading date and flowering time (Van Inghelandt et al, 2012;Yang et al, 2013Yang et al, , 2014Li et al, 2016d;Ye et al, 2018), plant height related (Dell'Acqua et al, 2015;Farfan et al, 2015;Li et al, 2016c), leaf architecture (Yang et al, 2014;Xue et al, 2016), leaf senescence (Fang et al, 2016), husk traits (Cui et al, 2016), grain shape and weight (Si et al, 2016;Duan et al, 2017;Liu et al, 2017), nitrogen use efficiency (Li et al, 2018c;Yu et al, 2020), grain protein content (Yang et al, 2019), eating and cooking quality (Wang et al 2017b), and taste and flavor (Tieman et al, 2017;Zhu et al, 2018). In addition GWAS was also used to identify the genetic determinants for diversity of plant nutrient metabolites, including thiamine, riboflavin (Li et al, 2018a), ascorbate (Ye et al, 2019), tocopherol and tocotrienol (Almeida et al, 2011;Wang et al, 2015), anthocyanin (Schulz et al, 2016;Wang et al, 2020), carotenoid (Schulz et al, 2016), and amino acid (Angelovici et al, 2013;Sun et al, 2020).…”
Section: Breeding With Genome Editingmentioning
confidence: 99%
See 1 more Smart Citation
“…The elucidation of the genetic determinants of the diversity of important traits through GWAS can help us to identify strong alleles and provides a theoretical basis for us to obtain biofortified crops and on agriculturally important traits such as shoot apical meristem (Leiboff et al, 2015), heading date and flowering time (Van Inghelandt et al, 2012;Yang et al, 2013Yang et al, , 2014Li et al, 2016d;Ye et al, 2018), plant height related (Dell'Acqua et al, 2015;Farfan et al, 2015;Li et al, 2016c), leaf architecture (Yang et al, 2014;Xue et al, 2016), leaf senescence (Fang et al, 2016), husk traits (Cui et al, 2016), grain shape and weight (Si et al, 2016;Duan et al, 2017;Liu et al, 2017), nitrogen use efficiency (Li et al, 2018c;Yu et al, 2020), grain protein content (Yang et al, 2019), eating and cooking quality (Wang et al 2017b), and taste and flavor (Tieman et al, 2017;Zhu et al, 2018). In addition GWAS was also used to identify the genetic determinants for diversity of plant nutrient metabolites, including thiamine, riboflavin (Li et al, 2018a), ascorbate (Ye et al, 2019), tocopherol and tocotrienol (Almeida et al, 2011;Wang et al, 2015), anthocyanin (Schulz et al, 2016;Wang et al, 2020), carotenoid (Schulz et al, 2016), and amino acid (Angelovici et al, 2013;Sun et al, 2020).…”
Section: Breeding With Genome Editingmentioning
confidence: 99%
“…Vitamin C can be transported between distinct organelles. Vitamin C is synthesized in the mitochondria, but is distributed throughout the cell, with a robust accumulation in the chloroplast (Wheeler et al, 1998; Critchley and Smirnoff, 2000; Zechmann et al, 2011). This implies that vitamin C is transported from the mitochondria to the chloroplasts.…”
Section: How Do Plants Produce Vitamins?mentioning
confidence: 99%
“…Specifically, the GO terms regulation of response to salt stress (GO:1901000; DE genes), regulation of response to osmotic stress (GO:0047484; DE genes and DE transcripts), response to water (GO:0009415; DE transcripts), lateral root formation (GO: 0010311; DE genes and DE transcripts), and root cap development (GO:0048829; DE transcripts) associate with root formation and growth (Ogawa & Yamauchi, 2006;Habte et al, 2014;Alahmad et al, 2019;Berhin et al, 2019;Kreszies et al, 2020;Ouertani et al, 2021). The GO terms regulation of starch metabolic process (GO:2000904; DE transcripts), amylase activity (GO:0016160; DTU transcripts), pigment metabolic process (GO:0042440; DAS genes) and pigment biosynthetic process (GO:0046148; DAS genes) are important to caryopsis development (Pagano et al, 1997;Lin et al, 2008;Shaik et al, 2016;Wang et al, 2020;Mackon et al, 2021). Therefore, the reductions of DE, DAS, and DTU genes and transcripts by using cRTD can also lead to a drop in important GO terms in the functional analysis.…”
Section: Differential Expression and Asmentioning
confidence: 99%
“…A few QTLs associated with PC in rice have been reported using biparental QTL analysis ( Sweeney et al, 2006 ; Wang and Shu, 2007 ; Dong et al, 2008 ; Maeda et al, 2014 ). With the rapid development of genome sequencing technology, a genome-wide association study (GWAS) based on linkage disequilibrium (LD) in a diverse natural population and using highly dense markers, such as single-nucleotide polymorphisms (SNPs), has been developed and proved to be a powerful approach for identifying genes that control complex traits, such as PC in rice, on a large scale ( Wang et al, 2020 ). Using the GWAS approach, more QTLs for PC were identified in rice ( Huang et al, 2010 ; Shao et al, 2011 ; Wang et al, 2016 ; Yang et al, 2018 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of genome sequencing technology, a genome-wide association study (GWAS) based on linkage disequilibrium (LD) in a diverse natural population and using highly dense markers, such as single-nucleotide polymorphisms (SNPs), has been developed and proved to be a powerful approach for identifying genes that control complex traits, such as PC in rice, on a large scale ( Wang et al, 2020 ). Using the GWAS approach, more QTLs for PC were identified in rice ( Huang et al, 2010 ; Shao et al, 2011 ; Wang et al, 2016 ; Yang et al, 2018 ; Wang et al, 2020 ). Huang et al (2010 , 2011) identified three QTLs associated with PC and two genes, Os02g0650900 and Os08g0301500 , encoding glutamate dehydrogenase and sucrose-phosphate synthase, were considered to be candidate genes underlying QTLs on chromosomes 2 and 8, respectively.…”
Section: Introductionmentioning
confidence: 99%